Analysis of the epidemiological profile of hospitalizations for varicose veins of the lower extremities from 2018 to 2022: a quantitative and comparative overview in Brazil - Macedo, Ariane Nascimento; Lopes, Cícero Fidelis (Revista de Medicina, 2023)
The clinical, surgical and socioeconomic relevance of varicose veins in the lower limbs is a point of resonance for the investigation of this condition, which has a wide impact on patients and society. The study aims to outline the epidemiological profile of hospitalizations for this venous pathology through a quantitative and comparative analysis between the five Brazilian regions. From the DATASUS consultation, from January 2018 to May 2022, ICD-10, race/color, sex, age, number, character, total amount of hospitalizations and average length of stay were analyzed. The total number of hospitalizations was higher for females with 151011 hospitalizations. In the age group of 50 to 59 years, for females with 44070 admissions. The white race/color, in females, has a higher number of hospitalizations with 25570 hospitalizations. The Southeast region concentrates 57.14% of the total number of hospitalizations and holds most of the total hospitalization values. The Northeast region had high averages of permanence, in terms of urgency, above 12; 12; 10; 8 and 6, in females, and values above 18; 14; 14; 10 and 10, in males, from 2018 to 2022 respectively.